Predictors of Visual Response to Intravitreal Bevacizumab for Treatment of Neovascular Age-Related Macular Degeneration - Kai Fang; Jun Tian; Xueying Qing; Shuai Li; Jing Hou; Juan Li; Wenzhen Yu; Dafang Chen; Yonghua Hu; Xiaoxin Li (Journal of Ophthalmology)
Purpose. To identify the predictors of visual response to the bevacizumab treatment of neovascular age-related macular degeneration (AMD). Design. A cohort study within the Neovascular AMD Treatment Trial Using Bevacizumab (NATTB). Methods. This was a multicenter trial including 144 participants from the NATTB study. Visual outcomes measured by change in visual acuity (VA) score, proportion gaining ≥15 letters, and change in central retinal thickness (CRT) were compared among groups according to the baseline, demographic, and ocular characteristics and genotypes. Results. Mean change in the VA score was 9.2 ± 2.3 SD letters with a total of 46 participants (31.9%) gaining ≥15 letters. Change in median CRT was −81.5 μm. Younger age, lower baseline VA score, shorter duration of neovascular AMD, and TT genotype in rs10490924 were significantly associated with greater VA score improvement (P=0.028, P<0.001, P=0.02, and P=0.039, resp.). Lower baseline VA score and TT genotype in rs10490924 were significantly associated with a higher likelihood of gaining ≥15 letters (P=0.028, and P=0.021, resp.). Conclusions. Baseline VA and genotype of rs10490924 were both important predictors for visual response to bevacizumab at 6 months. This trial is registered with the Registration no. NCT01306591.